TERRITORIAL BEHAVIOUR AND AGGRESSION OF ATHLETES IN RELATION TO THEIR RESILIENCE LEVEL - Csukonyi, Csilla; Ágoston, Márton (Stadium - Hungarian Journal of Sport Sciences, 2023)
We examined athletes’ territorial behavior and aggression and their relationship with resilience. The sample consists of 116, mainly amateur athletes. Our results show a significant positive relationship between territorial need and aggression but only in 'non-material territorial need' from the territorial subscales. Furthermore, we found no significant difference in the relationship between territorial need and aggression comparing individual and team athletes. Resilience was a non-significant mediator between territorial need and aggression. The results may provide helpful information for practitioner specialists and researchers in the applied field, as they both support previous research and attempt to address a new research topic.